TCSC control of power system oscillation and analysis using eigenvalue techniques - Mustafa, Mohd. Wazir (International Association of Computer Science and Information Technology Press (IACSIT), 2009)
TCSC devices are used to improve real power and eliminate line loses in ac systems. An additional task of TCSC is to increase transmission capacity as result of power oscillation damping. In this paper eigenvalue-based methods for analysis and control of power system oscillations using TCSC have been developed. The characterization of power system oscillations using the eigenvalues and eigenvectors of the state matrix is detailed. Design of power system damping controllers using residue method is addressed for two area four machine systems. The result shows the effectiveness of the method used